DETERMINANTS OF THE INTENTION TO PURCHASE ADVERTISED BANKING PRODUCTS - Burhanudin Burhanudin; Nurpatria Puspayudha Putranagara Mahardhika; Bagus Suminar; Rahman Recha Rahmad Simanjuntak; Heny Safitri Hudan Ningrum (Jurnal Ekonomi, 2023)
Advertisement is a common way for banks to sell their products. So, it's important to find out why people want to buy the things that are advertised. The purpose of this study is to investigate how subjective norms, attitude, perceived behavioral control, advertising value, and electronic word of mouth (eWOM) affect the intention to purchase advertised banking products. Then, a survey was conducted to test these factors, and as many as 227 individuals took part in the survey. The results showed that advertising value and eWOM had a significant effect on how likely customers were to buy bank products that were advertised. This study did not find that subjective norms, attitude, and perceived behavioral control had any effect on the intention to buy. If marketers of banking products want people to buy the advertised product, they need to make ads that help people understand the advertised product and spread the word about it among customers.